Survey of Court Judgments Using Data Mining - Aastha Budhiraja, Dr. Kamlesh Sharma (International Journal of Advanced Science and Technology, 2020)
With the world going around with computing and digitization, Legal department is one of the upcoming areas with opportunities to innovate. This paper delivers various techniques and usages to identify the relatedness of the case documents in this domain. A proposition to naturally recognize contentions in legitimate documents displayed. In this approach, cluster techniques are connected to argumentative sentences arrange to recognize contentions. One potential issue with this system is that a factious sentence belonging to one particular contention can moreover at the same time be part of another, particular argument. Law judgments are much elaborated which contains references of others. Inquire about endeavors are going on to  create  strategies  for  productive  look  of significant legitimate data by expanding the prevalent approaches utilized in data recovery and web looking investigate regions.